2017
DOI: 10.4103/ccd.ccd_576_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet irradiation on the osseointegration of a titanium alloy with bone

Abstract: Introduction:Attempt has been made to analyze the potential of titanium (Ti) alloy for osteointegration by the effect of surface photo functionalization in different aspects as follows: in Ringer's solution, in vitro cell growth, and in vivo study on rabbit. The present study was aimed to investigate the influence of ultraviolet (UV) light on surface topography, corrosion behavior, and bioactivity of indigenously manufactured samples of Ti alloy mini-implant.Materials and Methods:The study includes surface mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Titanium is one of the materials mostly used in this field. It has a good biocompatibility, is relatively inert, and is defined by surface features such as topography, roughness, and hydrophilicity that support cell growth and differentiation, influence the protein adsorption of the device implant and its immobilization (Gittens et al, 2014;Liu et al, 2017;Selders et al, 2017;Yadav et al, 2017). One of the primary aims of research in dentistry has been to improve the bone-implant interface and the titanium bioactivity by modifying its surface structure.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium is one of the materials mostly used in this field. It has a good biocompatibility, is relatively inert, and is defined by surface features such as topography, roughness, and hydrophilicity that support cell growth and differentiation, influence the protein adsorption of the device implant and its immobilization (Gittens et al, 2014;Liu et al, 2017;Selders et al, 2017;Yadav et al, 2017). One of the primary aims of research in dentistry has been to improve the bone-implant interface and the titanium bioactivity by modifying its surface structure.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that irradiating implants with ultraviolet (UV) light improves their associated cell growth and bone binding ability (osseointegration) [ 1 , 2 ]. Irradiating the surface of titanium (Ti) or titanium alloy (Ti6Al4V) with ultraviolet rays of a short wavelength improves the material’s osseointegration capacity.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ashish Yadav [77] the biological medium does not cause major corro- The images of the hFOB 1.19 cells incubated with Ag:HAp/Ti and Ag:Hap + D3/Ti thin films before and after UV irradiation for 24 h emphasized that the hFOB 1.19 cells exhibited a normal morphology and also revealed that the coatings did not induce any significant changes in the hFOB 1.19 cells. The observations made by microscopic visualization of the cells incubated for 24 h with the Ag:HAp/Ti and Ag:Hap + D3/Ti thin films before and after UV irradiation are in good agreement with the quantitative MTT results of the in vitro assay, and evidenced that both all the investigated thin films presents a good biocompatibility and could be suitable for being further employed in the development of biomedical devices.…”
Section: Resultsmentioning
confidence: 98%
“…According to Ashish Yadav [77] the biological medium does not cause major corrosion of titanium and its alloy. On the other hand, previous studies [30][31][32]78] reported that the UV irradiation of the titanium or titanium alloys lead to a significant increase of the surface hydrophilicity and biological properties.…”
Section: Resultsmentioning
confidence: 99%